2023
DOI: 10.1210/endocr/bqad027
|View full text |Cite
|
Sign up to set email alerts
|

miR-223 Plays a Key Role in Obesogen-Enhanced Adipogenesis in Mesenchymal Stem Cells and in Transgenerational Obesity

Abstract: Exposure of pregnant F0 mouse dams to the obesogen tributyltin (TBT) predisposes unexposed male descendants to obesity and diverts mesenchymal stem cells (MSCs) toward the adipocytic lineage. TBT promotes adipogenic commitment and differentiation of MSCs, in vitro. To identify TBT-induced factors predisposing MSCs toward the adipocytic fate, we exposed mouse MSCs to TBT, the PPARγ-selective agonist rosiglitazone or the RXR-selective agonist LG-100268. Then we determined their transcriptomal profiles to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On the other hand, the decreased abundance of hsa-miR-223-3p could be attributed to the decreased expression of PPARγ. PPARγ is identi ed as a direct regulator of this miRNA in adipose tissue [45]. Given this study's ndings of reduced abundance of both PPARγ and hsa-miR-223-3p following kawakawa tea intake, it remains to be clari ed whether kawakawa tea has a modulatory impact on in ammation and related pathways by in uencing the hsa-miR-223-3p/PPARγ axis.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the decreased abundance of hsa-miR-223-3p could be attributed to the decreased expression of PPARγ. PPARγ is identi ed as a direct regulator of this miRNA in adipose tissue [45]. Given this study's ndings of reduced abundance of both PPARγ and hsa-miR-223-3p following kawakawa tea intake, it remains to be clari ed whether kawakawa tea has a modulatory impact on in ammation and related pathways by in uencing the hsa-miR-223-3p/PPARγ axis.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, it has been described that the dysregulation of lncRNA (long non-coding RNA) involved in glucose homeostasis such as Gm6277 or Gm10804 as well as in adipose accumulation (Rian) can persist up to the F4 male generation [ 64 ]. Similarly, miR-223, a key mediator of PPARγ-dependent macrophage alternative activation, was found to be overexpressed in F2 and F3 male descendants of TBT-exposed dams [ 65 ].…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…For example, Du and colleagues in 2020 [36] hypothesized that in mice, betaine, a natural compound commonly present in beet, shellfish, spinach, Swiss chard, and other leafy green vegetables [36], can interact with gut microbiota-derived miR-378a and improve obesity since the miR-378a family acts as a regulator of numerous metabolic pathways, including autophagy and mitochondrial metabolism [53]. Likewise, more recently, Chen and collaborators (2022) [47] investigated the response of miR-143 in the presence of betaine in lipid metabolism. In wild-type mouse liver, it was observed that the expression of miR-143 was downregulated when betaine was supplemented.…”
Section: Roles Of Micrornas In Obesitymentioning
confidence: 99%
“…In wild-type mouse liver, it was observed that the expression of miR-143 was downregulated when betaine was supplemented. Also, the supplementation with betaine and miR-143 knockout caused obesity attenuation due to the repression of the glycoprotein nonmetastatic melanoma protein B (GPNMB), which has been reported to promote lipogenesis in white adipose tissue (WAT) and intensify diet-induced obesity [47,54]. Furthermore, fatty acid synthase (FASN) was upregulated when miR-143 was knocked out; nevertheless, FASN was observed to be downregulated when miR-143 knockout was supplemented with betaine.…”
Section: Roles Of Micrornas In Obesitymentioning
confidence: 99%
See 1 more Smart Citation